Dynamic phenomena in magnetic ternary alloys - Vatansever, Erol; Yüksel, Yusuf (Journal of alloys and compounds, 2016)
We apply Monte Carlo simulation with local spin update Metropolis algorithm to investigate dynamic critical phenomena in a magnetic ternary alloy system with the chemical formula ABpC1−p comprising ferromagnetic and antiferromagnetic exchange interactions simultaneously. We perform a detailed investigation of the critical behavior of the system by presenting the phase diagrams in various planes and corresponding thermal and magnetic features as functions of several adjustable parameters, such as the temperature, mixing ratio p and external field amplitude h0. We also revisit the equilibrium critical phenomena of the system which were previously handled by several theoretical tools and we re-examine former, widely studied properties. It is a fact that magnetic ternary alloy system has a special point at which the phase transition temperature of the system becomes independent of mixing ratio of ions B and C in equilibrium. However, our detailed results explicitly show that when a magnetic ternary alloy system is subject to a periodically driven time-dependent magnetic field, special point character of system tends to disappear, and hereby dynamic phase transition characteristics of the system begin to depend on the active concentrations of magnetic components. •We investigate ternary alloy structure under a time dependent magnetic field.•Monte-Carlo simulation with Metropolis algorithm is used.•A number of interesting phenomena have been found.